2012
DOI: 10.1074/jbc.m111.313130
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidate Phosphatase Plays Role in Zinc-mediated Regulation of Phospholipid Synthesis in Yeast

Abstract: Background:In yeast, phospholipid synthesis is regulated by zinc deficiency. Results: PAH1-encoded phosphatidate phosphatase activity was induced in zinc-deficient cells by a transcriptional mechanism. Conclusion: The zinc-mediated regulation of phosphatidate phosphatase affects phospholipid synthesis by controlling phosphatidate and diacylglycerol. Significance: The transcriptional regulation of phosphatidate phosphatase plays an important role in controlling phospholipid synthesis by zinc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
61
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 73 publications
(133 reference statements)
1
61
0
Order By: Relevance
“…ATP and CTP, nucleotides that serve as precursors in membrane phospholipid synthesis (5,6), inhibit PAP activity by a complex mechanism that affects catalytic efficiency and by chelation of Mg 2ϩ (57). Expression of the PAP-encoding gene PAH1 is regulated by growth phase and nutrient availability (13,58). Its expression is induced as yeast cells progress into the stationary phase when TAG synthesis is increased at the expense of membrane phospholipids (11), and the growth phase regulation is enhanced by inositol supplementation (13,58).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…ATP and CTP, nucleotides that serve as precursors in membrane phospholipid synthesis (5,6), inhibit PAP activity by a complex mechanism that affects catalytic efficiency and by chelation of Mg 2ϩ (57). Expression of the PAP-encoding gene PAH1 is regulated by growth phase and nutrient availability (13,58). Its expression is induced as yeast cells progress into the stationary phase when TAG synthesis is increased at the expense of membrane phospholipids (11), and the growth phase regulation is enhanced by inositol supplementation (13,58).…”
mentioning
confidence: 99%
“…Expression of the PAP-encoding gene PAH1 is regulated by growth phase and nutrient availability (13,58). Its expression is induced as yeast cells progress into the stationary phase when TAG synthesis is increased at the expense of membrane phospholipids (11), and the growth phase regulation is enhanced by inositol supplementation (13,58). The PAH1 expression is also induced when exponential phase cells are deprived of the essential mineral zinc.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of DGK1 does not impart a striking phenotype under standard laboratory culture conditions, but its overexpression causes many of the pah1⌬ phenotypes that are attributed to an elevated PA content (1). Of the transcriptional (71,77) and biochemical (49, 78 -81) mechanisms that control Pah1 PA phosphatase, phosphorylation/dephosphorylation (19, 44 -48, 66, 82) has the greatest impact on the functional role of the enzyme in lipid metabolism. In this work, we showed that Dgk1 DAG kinase, which counteracts the function of Pah1 PA phosphatase in controlling the levels of PA and DAG, is also phosphorylated and regulated by CKII.…”
Section: Discussionmentioning
confidence: 99%